ANALISIS NUMERIK PENGARUH KECEPATAN TERHADAP SEAKEEPING KAPAL PATROLI PADA DAERAH PELAYARAN SEASTATE 7 - Mohammad Taufik Ar Rozi; Betty Ariani; Dedy Wahyudi (ALE Proceeding, 2021)
Patrol boat is designed not to be slow in its movement on the water surface. To be able to move quickly and agilely, the most important requirement for this type of ship is in its maneuverability. The ship's motion at sea (seakeeping) is influenced by several things, speed, body shape, and the direction of the ship's heading waves. In this study, we analyze the six degrees of freedom, especially on the response of the ship's vertical movement, namely rolling on the sea waves of Seastate 7, especially in extreme weather in the South China Sea. The standard limit used is NORDFORSK 1987 with Light Manual Work Criteria. By entering parameters such as variations in speed and wave angle, such as 0°, 45°, 180° and 270°, then from the graph it can be seen the critical value for each movement. The calculation is carried out with the help of computational software Maxsurf Motions Advanced 20 V8i. The results of this study are the maximum roll movement value that occurs at a speed of 14 knots with a wave angle of 45° with a roll angle value of 6.40o. Furthermore, there is a decrease in the value of the movement along with the increase in the speed of the ship. The minimum roll value occurs when the wave angle is 270° when the ship's speed is 28 knots with a value of 5.69o.